Influence of tested parameters on biodiesel quality obtained from used and unused vegetable oil - Nuhanović, Mirza; Memić, Semir; Sušić, Edita; Smječanin, Narcisa (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2018)
The aim of this study was to obtain biodiesel, synthesized by transesterification from used (waste) and unused (industrial) sunflower vegetable oil, purify with following solvents: distilled water, 4% H3PO4 and 4% HCl, determine biodiesel quality parameters, and finally analyze the influence of the selected parameters and used solvents for purification on the content of soap in biodiesel. Rinsing of biodiesel for each used solvent was carried out 2, 3, 5, 7 and 9 times with a certain amount of above-mentioned solvents. Differences in the values of selected parameters (indicators) of biodiesel quality as well as the concentration of soap in the purified biodiesel between single rinses for the used solvents were observed, and the values of the examined parameters between different purifiers with the same rinse number were compared. In this study, the estimated effects of washing methods on biodiesel density, kinematic viscosity, acid number, peroxide number, flash point, and biodiesel synthesis yield were determined. It was found that there were no significant changes and deviations of the obtained values of the examined parameters, when purifying biodiesel with different solvents (for both type of used oils), except for the value of the peroxide number for acid washing. Based on the results obtained in this work, acid solution is better for soap removal.